PENGARUH GALLERY WALK TERHADAP MINAT BELAJAR SEJARAH DI SMAN 1 NATAR - Kahayun Kahayun; Wakidi Wakidi; Yustina Sri Ekwandari (PESAGI (Jurnal Pendidikan dan Penelitian Sejarah), 2015)
This research is aimed to investigate the effect of using Gallery Walk learning models on students interest in learning based on the subject of history class XI IIS 3 at SMA Negeri 1 Natar Academic Year 2014/2015. The type of this research is population research which class XI IIS 3 at SMA Negeri 1 Natar Academic Year 2014/2015 as the subject research. This research used quasi-experimental method while the technique of analyzing data using descriptive quantitative. The technique of collecting data were observation, questionnaire, documentation and literature. From the results of this research, can be concluded that the effect of using Gallery Walk learning models of students interest in learning based on the subject of history class XI IIS 3 at SMA Negeri 1 Natar Academic Year 2014/2015 is sufficient at 73, 22%. It is known by the average result of students interest in learning for three times experimental application of Gallery Walk learning models.Tujuan penelitian ini adalah untuk mengetahui bagaimanakah pengaruh penggunaan model pembelajaran Gallery Walk terhadap minat belajar siswa kelas XI IIS 3 pada Mata Pelajaran Sejarah di SMA Negeri 1 Natar Tahun Pelajaran 2014/2015. Penelitian ini adalah penelitian populasi dengan subjek terpilih adalah siswa kelas XI IIS 3 di SMA Negeri 1 Natar Tahun Pelajaran 2014/2015. Metode penelitian yang digunakan adalah metode eksperimen semu dengan teknik analisis data deskriptif kuantitatif. Teknik pengumpulan data melalui observasi, angket, dokumentasi dan kepustakaan. Dari hasil penelitian dapat disimpulkan bahwa pengaruh penggunaan model pembelajaran Gallery Walk terhadap minat belajar siswa kelas XI IIS 3 di SMA Negeri 1 Natar Tahun Pelajaran 2014/2015 adalah sedang sebesar 73, 22%. Hasil ini diketahui berdasarkan rata-rata minat belajar siswa selama tiga kali eksperimen penerapan model pembelajaran Gallery Walk.Kata kunci: gallery walk, minat belajar, pelajaran sejarah